THE IMPLEMENTATION OF CLOUD COMPUTING AS STRATEGIC TECHNOLOGY FOR SUSTAINABLE DEVELOPMENT USING REGRESSION ANALYSIS - Arora, Minit; Sharma, Vaibhav; Makkar, GD; Semwal, Pradeep; Sharma, Harish Chandra; Kero, Archana (The journal of contemporary issues in business and government, 2023)
As information technology has advanced, there has been a shift toward relying more and more on online cloud storage and computing services. There is no getting around the fact that recent times have seen a meteoric rise in interest in cloud computing. This technology is used by many different organisations as the central component of their information technology infrastructure. The use of cloud computing results in increased data processing efficiency across a variety of computer and storage systems that are available over the internet. The approaches have advanced as a direct result of the cutting-edge and forward-thinking computer procedures that are the foundation of the internet's core database and network architecture. In the 1990s, a new sort of cutting-edge computing known as grid computing came into being. 2005 saw the birth of two new computing paradigms: cloud computing and utility computing. Consolidating several virtual computing components into a single physical platform is one of the most distinguishing features of cloud computing services and infrastructure. These components include the central processing unit (CPU), the network, storage, and memory. A piece of software known as a hypervisor is responsible for isolating each virtual machine (VM) (used by Virtual box and VMware, for example). Using this strategy, one virtual disc or machine may be prevented from directly accessing the memory and programmes of another inside the same environment. This can be accomplished by using a firewall. Through the use of hardware abstraction, it is feasible to conceal the complexity of operating physical computer systems, while at the same time efficiently boosting the systems' processing capacity. Utilizing virtualization technology in the cloud comes with a number of benefits, including scalability and the capacity to support many tenants (one software programme serving many users at once). These properties are essential to cloud computing because they make sharing and pooling resources possible. Sharing and pooling resources provides a number of benefits, some of which include increased business value, more flexibility, and cost savings. When it comes to the process of moving assets from cloud providers to cloud virtualization users, provisioning is an extremely important step. In order to fulfil the requirements of its clientele, the cloud service provider must create an acceptable number of virtual machines and make available sufficient amounts of resources. This may be accomplished by any one of the following three methods: advanced provisioning, dynamic provisioning, or user self-provisioning. The mechanism by which cloud services and resources are made available, known as dynamic provisioning, faces a number of challenges. These challenges include the correct configuration of virtual machines (VMs) and technological constraints such as disc space, processing power, memory, and network throughput. It's possible that the scalability of virtual machines, the setup of cloud systems, and other aspects of virtualization's deployment might provide some difficulties.